Implementation Fuzzy C-Means on Decision Support System BPNT (Bantuan Pangan Non-Tunai) Ministry of Social Affairs Indonesia - Aji Setiawan; Akbar, Jordan Nur (EMITTER International Journal of Engineering Technology, 2019)
Decision Support System can be an alternative solution to determine the candidate's decision. Bantuan Pangan Non-Tunai (BPNT) are selected based on criteria determined by the Ministry of Social Affairs of the Republic of Indonesia. BPNT recipients are conducted by the government to help someone who is less able to meet their daily needs. The occurrence of errors in determining the eligibility of prospective beneficiaries is a major problem, based on these problems there needs to be an information system that can provide a valid BPNT recommendation and one of which uses a grouping method with the Fuzzy C-Means (FCM) algorithm. System development using the waterfall method. The results of system implementation and testing showed that 90% of the system was following what was expected according to the results of the test with the system being built.